Preaching to convert : evangelical outreach and performance activism in a secular age - Fletcher, John, 1975- (The University of Michigan Press, 2013)
'Preaching to Convert' offers an intriguing new perspective on the outreach strategies of US evangelicals. Author John Fletcher frames these activities, from door-to-door proselytising to the spirited sermons of superstar televangelists, as examples of activist performance, broadly defined here as acts performed before an audience in the hopes of changing hearts and minds.